The Level of Quality of Life of Preclinic Students of Dental Medicine - Farha, Nawwal Jaddiyya; Rahmawati, Ranti Sita; Ramadhan, Galang; SM, Rizky Briliant; Panjaitan, Ingrid Theresia; Olivia, Keyona Laila; Ramadhani , Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Background: Quality of life (quality of life) is an individual’s perception of his position in life and is related to goals, expectations, standards, and attention in life. Some research abroad has proven that students majoring in health have an interest in perfectionism and have high expectations of the intended achievements for improving the quality of life. Method: This research was a descriptive study with a sample of preclinical students of Universitas Airlangga. This research instrument consisted of a WHO-QOL questionnaire of 14 questions. The final results would be collected in the form of tables and percentages. Results: In this study obtained 78 respondents (66 women, 12 men) from 4 preclinical forces (2016: 5 people, 2017: 24 people, 2018: 16 people, and 2019: 33 people). Of both groups, 79.5% of students had a good quality of life and 20.5% of them were poor. Where 64.5% of respondents with good quality of life were in the younger generation, and 35.5% of them were older generation. Poor quality of life was found in 7 students from the older generation (43.8%) and 9 young people (56.3%). Conclusion: The quality of life of preclinical students of the Dental Medicine Faculty of Universitas Airlangga was quite good, and no significant differences were found in the duration of the study with quality of life.